Wasabi - Japanese Horseradish (Bangladesh Journal of Scientific and Industrial Research, 2009)
Wasabi, Japanese Horseradish (Wasabia japonica (Miq.) Matsum) is a perennial plant native to Japan. It has been cultivated in Japan for more than a thousand years and is now being grown in many countries as interest in Japanese cuisine expands. Wasabi can be grown in two main ways, either in flooded fields or in soil based mediums. The unique flavour of wasabi comes from isothiocyanates (ITCs) which are evolved from precursor glucosinolates by the enzyme myrosinase when the tissue is disrupted. ITCs found in wasabi are volatile, possess strong pungent smells and are toxic at high intakes. The overall flavour of wasabi depends on individual ITC content. Allyl ITC is found in the highest concentration in all tissues, ranging from 86-92% of the total ITC content. Apart from flavouring sauces and foods wasabi isothiocyanates have interesting anticancer effects. ITCs can also counter inflammatory conditions like asthma and anaphylaxis. ITCs have also been shown to inhibit platelet aggregation in the blood. Wasabi is a valuable crop that can be processed into a tasty condiment. Its production and consumption will increase as it becomes more appreciated in Western cuisine. Keywords: Wasabia japonica, Horseradish, Flavour compounds, Isothiocyanate (ITC), Glucosinolate, Allyl ITC, 3-butenyl ITC, 4-pentenyl ITC, 5-hexenyl ITC, 2-pheneylethyl ITC, Isopropyl ITC, Secbutyl ITC, Rhizome, Anticancer, Anti-asthmatic, Anti-inflammatory, Industrial application doi: 10.3329/bjsir.v43i4.2234 Bangladesh J. Sci. Ind. Res. 43(4), 433-448, 2008